IDENTIFIKASI DAN PENILAIAN RISIKO K3 DI AREA STONE CRUSHER YANG BEROPERASI DI PRAFI, KABUPATEN MANOKWARI, PROVINSI PAPUA BARAT - Pribowo Angling Kusumo (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2020)
Zero accident policy that proclaimed by the Government through the Ministry of Manpower and Transmigration must be implemented properly by all companies that operating in Indonesia. Zero accident can be accomplished by implemented Health and Safety in work (K3) and risk management in all companies, both small and large scale companies. The stone crusher company which operates in Prafi plain, Manokwari Regency, West Papua Province, is a high capital and high company with substantial assets, accidents might have happened during work projects. Assessment of the risk level of a stone crusher project can be done by conducting interviews, identification, observation and research to determine risk factors that may occur during work projects. The analysis shows that the stone crusher project has a low risk level (12%), moderate (39%) to high risk (49%). The high risk level percentage (49%) makes the stone crusher company obliged to carry out K3 management and risk control by involving K3 experts in every work project so that zero accident can be achieved.